Stability of floxuridine and leucovorin calcium admixtures for intraperitoneal administration - Smith, J A; Morris, A; Duafala, M E; Bertino, J R; Markman, M; Kleinberg, M (American journal of hospital pharmacy, 1989)
The stability of floxuridine and leucovorin calcium in admixtures of 0.9% sodium chloride injection at various concentrations, temperature conditions, and time points was determined. Admixtures of floxuridine and leucovorin calcium were prepared in 1-L plastic bags containing 0.9% sodium chloride injection. Admixtures containing the following three concentrations were prepared: floxuridine 1 g and leucovorin calcium 30 mg, floxuridine 2 g and leucovorin calcium 240 mg, and floxuridine 4 g and leucovorin calcium 960 mg. The admixtures were stored at refrigerated temperature (4-8 degrees C), ambient room temperature (20 degrees C), and near-physiologic body temperature (40 degrees C). Drug concentrations were measured with a stability-indicating high-performance liquid chromatographic (HPLC) method at 0, 4, 8, 24, and 48 hours (4-8 degrees C) and at 0, 1, 3, 6, 24, and 48 hours (20 degrees C and 40 degrees C). A second set of samples at the same concentrations was prepared and sequentially stored at refrigerated, room, and near-physiologic temperatures to simulate actual-use conditions; these samples were assayed by HPLC at 0, 4, 8, 24, and 48 hours (4-8 degrees C); 49, 51, 54, and 60 hours (20 degrees C); and 61, 63, 66, and 72 hours (40 degrees C). All solutions were protected from light. Floxuridine and leucovorin calcium were stable at each concentration and temperature condition tested for a minimum of 48 hours. However, leucovorin calcium was more subject to decomposition at near-physiologic temperature than at other temperatures, with the most degradation at the lowest concentration.